Parental Assistance, Affection, and Conduct Modification in Adolescents: A Behavioral Scientific Perspective - Luhut Marisi Simanjuntak (Inspire Global Insight Journal, 2026)
Purpose of the study: Parental support and attachment quality are fundamental determinants of youth behavioral adjustment. Understanding these relationships through a behavioral science lens provides critical insights for intervention and prevention strategies. This study examined the relationships between parental support dimensions, attachment styles, and behavioral adjustment outcomes in adolescents, investigating mediating mechanisms through a comprehensive behavioral science framework. Materials and methods: A cross-sectional study was conducted with 847 adolescents (ages 12-18, M = 15.2, SD = 1.8) and their primary caregivers. Participants completed validated measures including the Parental Support Scale (PSS), Adult Attachment Interview-Revised (AAI-R), and Youth Behavioral Assessment Inventory (YBAI). Statistical analyses included correlation analysis, structural equation modeling, and mediation analysis. Results: Strong positive correlations were found between parental support and secure attachment (r = .72, p < .001) and between secure attachment and positive behavioral adjustment (r = .68, p < .001). Parental emotional support demonstrated the strongest predictive relationship with behavioral outcomes (β = .54, p < .001). Secure attachment partially mediated the relationship between parental support and behavioral adjustment (indirect effect = .31, 95% CI [.26, .37]). Conclusions: Findings confirm that parental support significantly influences youth behavioral adjustment through attachment mechanisms. Secure attachment serves as a crucial mediator, suggesting that interventions targeting parent-child relationships may effectively promote positive youth outcomes.